2023
DOI: 10.3390/jcm12072669
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Influence of State Anxiety on the Effect of Midazolam on Postsurgical Pain

Abstract: Anxiety contributes to postsurgical pain, and midazolam is frequently prescribed preoperatively. Conflicting results have been described concerning the impact of midazolam on pain. This study aims to evaluate the effect of systemic midazolam on pain after open inguinal hernia repair, clarifying its relationship with preoperative anxiety. A prospective observational cohort study was conducted in three Portuguese ambulatory units between September 2018 and March 2020. Variable doses of midazolam were administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Finally, a higher level of satisfaction in the MTG compared to the CG was reported, even if a recent publication reported that midazolam may influence postsurgical pain [48]. These results highlight that a MT intervention (with a certified music therapist) is not a case of simply listening to music, and instead allows the MTp to build an empathic relationship with the patient.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, a higher level of satisfaction in the MTG compared to the CG was reported, even if a recent publication reported that midazolam may influence postsurgical pain [48]. These results highlight that a MT intervention (with a certified music therapist) is not a case of simply listening to music, and instead allows the MTp to build an empathic relationship with the patient.…”
Section: Discussionmentioning
confidence: 80%
“…However, the results of current studies are not entirely consistent, due in part to diverse methodo-logical approaches, the use of different measurement tools for the variables studied, and definitions of treatment outcomes. Therefore, further research is needed to assess the effectiveness of prehabili-tation programs, with particular emphasis on longitudinal studies and aiming for some standardization of educational interventions while maintaining an individual approach to patients’ fears and anxieties, as well as patient satisfaction assessment [ 1 , 8 , 9 , 36 ].…”
Section: Summary and Directions For Future Researchmentioning
confidence: 99%
“…A preliminary study conducted among 65 patients awaiting cardiac surgery provided promising results regarding the reliability of the scale (Cronbach's a coefficient for the full scale was 0.93, for short-term aspects of surgery was 0.91, and for long-term surgery aspects was 0.90). The SFQ questionnaire has been used in studies conducted in the Netherlands [28,29], Greece [34], Portugal [35,36], Turkey [21,23,33,[37][38][39][40][41][42][43], Croatia [44], Norway [45], Germany [31], Italy [46], Czech Republic [30], China [32], United States [47,48], Ireland [49], and Hungary [50][51][52]. Most of these publications appeared in the years 2022-2023.…”
Section: Prospective Evaluation Monitoring the Level Of Anxietymentioning
confidence: 99%